Effect of Mutation of RNA-dependent RNA Polymerase (RdRp) of Hepatitis C Virus on Affinities of Dasabuvir: Computational Study: Pengaruh Mutasi RNA-dependent RNA polymerase (RdRp) pada Virus Hepatitis C terhadap Afinitas Dasabuvir: Kajian Komputasi - Arba, Muhammad; Wahyudi, Setyanto Tri (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2024)
Hepatitis C Virus (HCV) is one of the infectious diseases that has posed a serious threat to global public health for the past few decades. HCV is an RNA virus that infects the human liver and can lead to chronic liver damage, cirrhosis, and even liver cancer. Treatment for HCV infection has made rapid advancements in recent years, particularly with the development of more effective antiviral drugs. One of the drugs used in HCV therapy is dasabuvir. Dasabuvir is an RNA-dependent RNA polymerase (RdRp) inhibitor that functions to inhibit the replication of the HCV virus. The RdRp enzyme in HCV is represented by NS5B, and dasabuvir specifically targets this enzyme. Several reports have revealed mutations in HCV NS5B due to the use of dasabuvir. This study conducted a computational mutation analysis on NS5B of HCV resulting from dasabuvir usage. The research findings indicate that mutations in the HCV polymerase induced by dasabuvir usage lead to changes in dasabuvir's conformation and binding energy. Some mutations decrease binding energy, such as mutations C316N, C451S, and N411S. However, on the other hand, there are mutations that increase binding energy, such as M414V, A553V, and C445F. The decrease in binding energy is supported by increased hydrogen bonding interactions with Asp318, Gln446, and Tyr448, as well as the formation of new hydrogen bonds, such as hydrogen bonding with Ser288 in C451S and Arg200 in C451S. Meanwhile, the increase in binding energy is supported by decreased binding interactions with Asp318 and pi-pi interactions with Phe193. Hydrogen bonding with Asn291 also decreases, as seen in A553V, and is even lost in C445F. Future work will be devoted for designing new dasabuvir derivatives which having better affinited to NS5B of HCV.